ASSOCIATION BETWEEN VITAMIN D LEVELS IN SERUM WITH OUTCOME OF TUBERCULOUS MENINGITIS - Susanti, Restu; Putri, Fanny Adhy; Hardianti, Sonia (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: The most dangerous form of tuberculosis outside of the lungs, tuberculous meningitis (TBM) causes a lot of illness and even death. Vitamin D endures an important role, via stimulating antimicrobial peptides in the vitamin D receptor (VDR) signaling pathway, which in turn increases macrophage bactericidal activity against Mycobacterium TB, which are associated with the outcome of TB, including TBM. Objective: This research set intended to determine whether there was a connection between TBM patients' blood vitamin D levels and their subsequent health problems. Methods: Scores 4-5 on the Glasgow Outcome Scale (GOS) were used to classify positive clinical results, whereas scores 1-3 were used to classify negative outcomes. Serum vitamin D concentrations were quantified using the ELISA method. Results: The results of TBM patients were unrelated to their blood vitamin D levels (p = 1.000). Compared to the median blood vitamin D level of 51.97 ng/mL in the patients who did not survive, the median level in the patients who did survive was 71.11 ng/mL. When compared to results from individuals with normal blood vitamin D levels, TBM did not substantially vary (p = 0.454). Conclusion: There is evidence that vitamin D insufficiency increases the likelihood of contracting TB and worsens the disease in people who already have it.